Analisis Tata Kelola Website Pejabat Pengelola Informasi Dan Dokumentasi Dinas Komunikasi Informatika Statistik Dan Persandian Provinsi Banten Untuk Pelayanan Informasi Digital Studi Kasus Sistem Informasi Di Diskominfo SP Provinsi Banten - Tika Zulzana; Eli Apud Saepudin; Rizki Amilia (Universitas Serambi Mekkah, 2026)
Public information disclosure is one of the fundamental principles for achieving good governance through the utilization of information technology. The Public Information and Documentation Management Officer (PPID) website of the Department of Communication, Informatics, Statistics, and Cryptography of Banten Province serves as a digital information service platform designed to improve public accessibility, transparency, and accountability. This study aims to analyze the governance of the PPID website in supporting digital public information services at the Department of Communication, Informatics, Statistics, and Cryptography of Banten Province. The research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, documentation, and literature review, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the PPID website governance has contributed to the implementation of digital information services by providing periodic, immediate, and publicly available information in accordance with applicable regulations. Nevertheless, several challenges remain, including limited content updates, underutilized service features, insufficient information system integration, and low public participation in utilizing digital services. Therefore, strengthening website governance through improved human resource capacity, information system optimization, enhanced data security, and continuous evaluation is essential to create public information services that are more effective, efficient, transparent, accountable, and responsive to community needs.